Isolation and identification of caffeine-degrading bacteria from soil, coffee pulp waste and excreted coffee bean in Luwak feces - TOTO ISWANTO; MAYA SHOVITRI; ALI ALTWAY; TRI WIDJAJA; DINIHARI INDAH KUSUMAWATI; PUSPITA LISDIYANTI (Society for Indonesian Biodiversity, 2019)
Abstract. Iswanto T, Shovitri M, Altway A, Widjaja T, Kusumawati DI, Lisdiyanti P. 2019. Isolation and identification of caffeine-degrading bacteria from soil, coffee pulp waste and excreted coffee bean in Luwak feces. Biodiversitas 20: 1580-1587. The present study deals with the isolation and identification of caffeine-degrading bacteria obtained from the caffeine contaminated environment or caffeinated wastes. These bacteria are useful for various biotechnological applications especially in increasing the potential utilization of caffeinated wastes and producing the high-value chemicals. The suspected caffeine-degrading bacteria have been isolated from the soil of coffee plantation area, coffee pulp waste, and the excreted coffee bean in fresh feces of Luwak (Paradoxurus hermaphroditus or Asian Palm Civet) by growing them on the caffeinated agar medium (CAM) containing basal salt medium (M9) and caffeine as a sole source of carbon and nitrogen. CAM-supplemented with 1.5 to 10 g L-1 of caffeine has been used for screening of the potential bacteria which able to grow in high caffeine concentration. Molecular identification based on 16S rRNA gene sequence was performed to identify the selected bacteria. The result revealed that there were 11 and 3 strains of 12 selected bacteria which could grow on the CAM-supplemented with caffeine up to 7 and 10 g L-1, respectively. Based on 16S rRNA gene sequence and phylogenetic analysis, those bacteria were from 5 Gram-negative species, namely Pseudomonas japonica (4/12), Methylobacterium populi (5/12), Raoultella ornithinolytica (1/12), Klebsiella quasipneumoniae (1/12), and Stenotrophomonas chelatiphaga (1/12). Further investigations to determine their metabolic pathway, enzyme, and growth kinetics in the caffeinated medium may provide insights into its possible utilization for scientific or other applications.